Spectrophotmetric Micro determination of promrthazine hydrochloride in pharmaceutical - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
a simple accurate and sensitive spectrophotometric method for the determination of promethazine HCI has been developed the method is based on the oxidative coupling reaction of promethazine